The role of cultural context in interpreting pragmatic meaning (Research, Society and Development, 2026)
This study investigates how cultural background influences the interpretation and use of pragmatic meaning among university students specializing in semantics and pragmatics, all of whom are preparing for careers in teaching English as a foreign language. While these students possess foundational linguistic knowledge, there remains a gap in understanding how cultural variables affect the interpretation of indirect speech acts, politeness strategies, implied meanings, and figurative expressions. A total of 52 participants engaged in this mixed-method investigation conducted over four classroom sessions. Data collection involved Likert-scale self-assessments and performance-based multiple-choice tasks designed to assess both confidence and competence in pragmatic interpretation. Results showed that while students expressed moderate confidence, their actual responses revealed challenges in recognizing culturally embedded pragmatic cues. These findings highlight the importance of integrating explicit, culturally informed pragmatic instruction even in advanced linguistic programs. The study concludes with recommendations to better prepare future English teachers for cross-cultural communication challenges in their classrooms.